ANALISIS PENDAPATAN DAN NILAI TUKAR PETANI KARET RAKYAT DI DESA AIR SEKAMANAK KECAMATAN KETAHUN KABUPATEN BENGKULU UTARA - Arifin, Zaenal; Sriyoto, Sriyoto; Yuliarti, Ellys (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2012)
This research was aimed to estimate income from rubber farming folk and envistige rubber farmer buying power through term of trade indicators. This research is conducted at Village Air Sekamanak District Ketahun North Bengkulu. Eighty nine labourfarmers were selected using Stratified Random Sampling method. The result of this research found that the farmers terms of trade is 1.43 in May and 1.45 in June. These results indicate that in the month May and June of rubber farmers in the study area during the month were categorized into levels of prosperity.Average farm income of smallholder rubber farmers in the study area is Rp 1,945,690.37 Ut in May, while the average income in June amounted to Rp 1,945,117.34 Ut.